2012
DOI: 10.1088/0004-637x/757/1/2
|View full text |Cite
|
Sign up to set email alerts
|

Galaxies in X-Ray Groups. Ii. A Weak Lensing Study of Halo Centering

Abstract: Locating the centers of dark matter halos is critical for understanding the mass profiles of halos, as well as the formation and evolution of the massive galaxies that they host. The task is observationally challenging because we cannot observe halos directly, and tracers such as bright galaxies or X-ray emission from hot plasma are imperfect. In this paper, we quantify the consequences of miscentering on the weak lensing signal from a sample of 129 X-rayselected galaxy groups in the COSMOS field with redshift… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 72 publications
11
129
1
Order By: Relevance
“…3.2, using the same COSMOS data, George et al (2012) confirmed the findings of Jeltema et al (2007) about the BGG/BCG in groups and clusters: an early-type galaxy, but not necessarily a dominant one, and with observed shifts up to 100 kpc with respect to the X-ray peak (see also Hoekstra et al 2012, and their sample of 50 massive galaxy clusters). In our study of the SARCS sample, we observed the same behaviour in some specific cases such as the multi-modal groups where there is not a single early-type galaxy dominating the light distribution, and/or where the strong-lensing system is not associated to the brightest member.…”
Section: Comparison With Previous Worksupporting
confidence: 81%
See 2 more Smart Citations
“…3.2, using the same COSMOS data, George et al (2012) confirmed the findings of Jeltema et al (2007) about the BGG/BCG in groups and clusters: an early-type galaxy, but not necessarily a dominant one, and with observed shifts up to 100 kpc with respect to the X-ray peak (see also Hoekstra et al 2012, and their sample of 50 massive galaxy clusters). In our study of the SARCS sample, we observed the same behaviour in some specific cases such as the multi-modal groups where there is not a single early-type galaxy dominating the light distribution, and/or where the strong-lensing system is not associated to the brightest member.…”
Section: Comparison With Previous Worksupporting
confidence: 81%
“…For instance, Jeltema et al 2007 have studied a sample of seven X-ray-loud galaxy groups at intermediate redshifts (0.2 < z < 0.6), and for two of them, the brightest galaxy presents an offset ∼100 h −1 70 kpc with the X-ray emission peak. They also found two groups where no dominant elliptical galaxy is present, but rather several ones with comparable luminosities (see also the more recent work by George et al 2012, of the COSMOS X-ray-selected groups). In such cases, the assumption of tracing the mass centre by the position of the most luminous galaxy might be wrong as well.…”
Section: Choice Of the Centrementioning
confidence: 71%
See 1 more Smart Citation
“…Dietrich et al 2012;George et al 2012) that WL masses using lensing cluster centres are biased high due to random noise with respect to those based on independently obtained cluster centres, e.g. the ROSAT centres we employ.…”
Section: A3 Choice Of Centre and Fitting Rangementioning
confidence: 99%
“…One important aspect of how LRGs trace dark matter is how often they coincide with the centers of dark matter halos. The identification of central galaxies in cluster samples is critical for a variety of studies, including the determination of cluster halo masses with weak gravitational lensing (George et al 2012), and RSD studies (Hikage & Yamamoto 2013). Because LRGs are luminous and trace massive overdensities, it is often assumed that central galaxies are also LRGs.…”
Section: Introductionmentioning
confidence: 99%